If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + x = 11 + -2x Solving 5 + x = 11 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 5 + x + 2x = 11 + -2x + 2x Combine like terms: x + 2x = 3x 5 + 3x = 11 + -2x + 2x Combine like terms: -2x + 2x = 0 5 + 3x = 11 + 0 5 + 3x = 11 Add '-5' to each side of the equation. 5 + -5 + 3x = 11 + -5 Combine like terms: 5 + -5 = 0 0 + 3x = 11 + -5 3x = 11 + -5 Combine like terms: 11 + -5 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| 7m+48=-5m-16 | | 0=81x^2-16 | | x(6x-6)=(6x+1)(x-1) | | 92=3y+6y+20 | | -4b-5+2n=10 | | 2(3u+7)=-4(3+-2u) | | 5x-3(x-4)=-8+4x+12 | | 9+12n=-4n^2 | | 4(5x-8)+8=12-(6x-15) | | 41=32-t | | -9d-8=-2(d+4)-7d | | -8x=9y-6 | | 5(2q^4)= | | .5x-5=-1 | | 7=r-4 | | 3m^2-18m+25=1 | | 3.1(x+2)-15x=2(x-5) | | -2x+9.0=-18 | | 8x/6a+9-2d*5a-2x+4d | | -b^2+3b-1=0 | | X+50+x+32=1 | | 6x+4-5x=7+1 | | a^2+8=-6a | | -4r-5.5-1.5r+2.6r-4= | | 2(x-13/4) | | -4(8y-3)=-20 | | 2(x+4)-x=8 | | 16-12r=4y | | 9x-15+9x+30=x | | 3x=-2y-1 | | 1/3n-4(2/3n-3)=2/3n-6 | | 5.2+k=0.17 |